Flowering plant immune repertoires expand under mycorrhizal symbiosis. (5th March 2019) - Kramer, Eric M.; Statter, Samantha A.; Yi, Ho Jun; Carlson, Joseph W.; McClelland, Donald H. R.
Abstract: Immune perception in flowering plants is mediated by a repertoire of cytoplasmic and cell‐surface receptors that detect invading microbes and their effects on cells. Here, we show that several large families of immune receptors exhibit size variations related to a plant's competence to host symbiotic root fungi (mycorrhiza). Plants that do not participate in mycorrhizal associations have significantly smaller immune repertoires, while the most promiscuous symbiotic hosts (ectomycorrhizal plant species) have significantly larger immune repertoires. By contrast, we find no significant increase in immune repertoire size among legumes competent to form a symbiosis with nitrogen‐fixing bacteria (rhizobia). To explain these observations, we hypothesize that plant immune repertoire size expands with symbiote species diversity.